Д.НАЦАГДОРЖИЙН НЭГЭН ШҮЛГИЙН УРАН ЧАДВАРЫН АСУУДАЛД: "Минин ээж" (1935 он) шүлгийн жишээн дээр - Р.Бигэрмаа (Acta Mongolica, 2012)
In this article, defining stylistic method, form, feature and style of a certain poem of D. Natsagdorj have been analyzed and explained in a wide range. To sum up, language of his poem makes the poem melodically, logically and rhythmically: and head rhyme, internal rhyme and end rhyme and intonation built up the development of Mongolian poetry studies. To study the poem structure/’rhythm is very important in any poem. It can be said that every poem is written on the base of the rhythm and it is right that the rhythm will be checked at first to examine any poem.’* According to this, here is following things to emphasize the features of rhythm, beat and prosody. In Mongolian ancient literature, some characters such as gods, heavens, kings and high lamas, usually was depicted. But in Natsagdorj’s work, proclaiming the new life and new person in the way of depicting plain and real person, is revealed the character of “mother" in this poem. One of his poetry ’s peculiarities is filling and choosing the stylistics, ending the sentence by the parts of speech which are available and using mostly the metaphor which has sharp and clear imagery. From the D.Natsagdoij works, especially his poems of, there are no fixed ideas, iradilional written ibnn and stylislic influence ofancient written works vihich had a quiet influence to the literature of the early of the revolution. It is seen that he wrote his poems in literature language, stylistic and fbnnation of modern Mongolian and it is quite different from the written style, way of thinking and the classic and oral Mongolian language stylistics influence of present writers and poets.